2003
DOI: 10.1021/jf021034o
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Dietary Oregano Essential Oil and α-Tocopheryl Acetate Supplementation in Long-Term Frozen Stored Turkey Meat

Abstract: The effects of dietary oregano essential oil and alpha-tocopheryl acetate supplementation on the oxidative stability of long-term frozen stored turkey meat were investigated. Thirty 12-week-old turkeys, randomly divided into five groups, were given a basal diet or a basal diet supplemented with 200 mg of alpha-tocopheryl acetate kg(-1), or 100 or 200 mg of oregano oil kg(-1), or 100 mg of oregano oil plus 100 mg of alpha-tocopheryl acetate kg(-1) for 4 weeks prior to slaughter. Lipid oxidation in breast and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 45 publications
3
59
0
3
Order By: Relevance
“…Studies on beef confirmed the efficacy of an onion extract dietary supplement in reducing microbial contamination (Irkin and Arslan, 2010). Essential oils extracted from various spices and herbs were successfully used in animal feed to increase the oxidative stability of meat (Botsoglou et al, 2002(Botsoglou et al, , 2003(Botsoglou et al, , 2004. Soultos et al (2009) demonstrated that adding oregano oil to the diet of rabbits reduced total mesophilic aerobes, Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 90%
“…Studies on beef confirmed the efficacy of an onion extract dietary supplement in reducing microbial contamination (Irkin and Arslan, 2010). Essential oils extracted from various spices and herbs were successfully used in animal feed to increase the oxidative stability of meat (Botsoglou et al, 2002(Botsoglou et al, , 2003(Botsoglou et al, , 2004. Soultos et al (2009) demonstrated that adding oregano oil to the diet of rabbits reduced total mesophilic aerobes, Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 90%
“…The highly unsaturated nature of n-3 fatty acids predisposes the egg yolk and poultry meat to lipid oxidation (Botsoglou et al, 1997(Botsoglou et al, , 2002(Botsoglou et al, , 2003. By increasing the degree of unsaturation of the yolk lipid oxidation increases, and toxic oxidation products lower the quality and nutritional and organoleptic values of the animal product (Cherian et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of plant extract to poultry diet can have positive effect on carcass quality as well as the properties of stored meat quality [5]. Addition of flavonoids And the trepans (Azulan) contained in the essential oil have antioxidant properties which can influence on carcass quality after slaughtering and even as freeze during preservation period [6,7].…”
Section: Introductionmentioning
confidence: 99%